2008
DOI: 10.1149/1.2889011
|View full text |Cite
|
Sign up to set email alerts
|

Planar NASICON-Based CO[sub 2] Sensor Using BiCuVO[sub x]/Perovskite–Type Oxide as a Solid-Reference Electrode

Abstract: To improve the stability of a NASICON ͑Na 3 Zr 2 Si 2 PO 12 ; Na + conductor͒-based potentiometric CO 2 sensor under humid conditions, a composite of BiCuVO x ͑Bi 2 Cu 0.1 V 0.9 O 5.35 ͒ and perovskite-type oxide ͑La 0.6 Sr 0.4 Co 0.78 Ni 0.02 Fe 0.2 O 3 ͒ was used as a solidreference electrode. The CO 2 sensing properties and stability of a NASICON-based planar device fitted with Li 2 CO 3 -BaCO 3 ͑auxiliary phase͒ and the composite reference electrode were examined under humid conditions. The planar device m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Perovskite-type oxide La 0.6 Sr 0.4 Co 0.78 Ni 0.02 Fe 0.2 O 3 was prepared by an evaporation method. 32 The perovskite-type oxide powder was mixed with distilled water to form a paste, which was applied to one side of the GO membrane and dried at room temperature. The sensing and counter electrodes were exposed to the sample gases.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Perovskite-type oxide La 0.6 Sr 0.4 Co 0.78 Ni 0.02 Fe 0.2 O 3 was prepared by an evaporation method. 32 The perovskite-type oxide powder was mixed with distilled water to form a paste, which was applied to one side of the GO membrane and dried at room temperature. The sensing and counter electrodes were exposed to the sample gases.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…This value agrees well with the theoretical value of 76.7 mV per decade, which corresponds to the reaction electron number (n) ¼ 2.0. 20,21 The EMF of the device can be expressed as a function of the logarithm of CO 2 concentration (ppm) as follows:…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that the sensor device demonstrates slight responses to water vapor and high stability even under highly humid conditions. 21,33 Thus, a small amount of water at ppm concentrations formed by the combustion of VOCs does not interfere with the sensor response. In addition, the NASICONbased sensor has been shown to have high selectivity for CO 2 without interference from present gases such as NO x , SO x , CO, ethanol, ammonia, and hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ti þ TiH 2 is used as a reference electrode in hydrogen sensors for use in molten aluminum [125]. Humidity may cause degradation of reference electrodes, but stability can be improved by using mixed oxides, such as La 0.6 Sr 0.4 Co 0.78 Ni 0.02-Fe 0.2 O 3 [126]. The addition of mixed oxides, such as (La,Sr)MnO 3 [127], can be used to inhibit the sintering of porous electrodes, which also improves stability; the properties of such perovskites are briefly described in Chapter 9.…”
Section: Reference Electrodesmentioning
confidence: 99%